2007
DOI: 10.1177/1077558707305413
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Reduce Racial and Ethnic Disparities in Health Care

Abstract: In 2005, the Robert Wood Johnson Foundation created Finding Answers: Disparities Research for Change, a program to identify, evaluate, and disseminate interventions to reduce racial and ethnic disparities in the care and outcomes of patients with cardiovascular disease, depression, and diabetes. In this introductory paper, we present a conceptual model for interventions that aim to reduce disparities. With this model as a framework, we summarize the key findings from the six other papers in this supplement on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
221
0
6

Year Published

2008
2008
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 271 publications
(231 citation statements)
references
References 29 publications
4
221
0
6
Order By: Relevance
“…26,27 We found that most primary-care clinicians endorsed the collection of patients' race and ethnicity data to improve the quality of diabetes care, concordant with regulations in other settings that require hospitals to collect these self-reported data. 28 Whereas the vast majority recognized the existence of racial disparities within the U.S. health system, only slightly more than one third acknowledged their presence among patients they personally treat.…”
Section: Discussionmentioning
confidence: 84%
“…26,27 We found that most primary-care clinicians endorsed the collection of patients' race and ethnicity data to improve the quality of diabetes care, concordant with regulations in other settings that require hospitals to collect these self-reported data. 28 Whereas the vast majority recognized the existence of racial disparities within the U.S. health system, only slightly more than one third acknowledged their presence among patients they personally treat.…”
Section: Discussionmentioning
confidence: 84%
“…In mental health, however, little is known about the equity effects of quality improvement interventions (7), and most studies of these effects have focused on depressed populations (8,9). A review of quality improvement interventions for patients with depression and other chronic health conditions identified case management as a key ingredient of multicomponent approaches that improved quality and reduced disparities (10). …”
mentioning
confidence: 99%
“…The average DB score of 213 studies included in the first set of systematic reviews commissioned by the Robert Wood Johnson foundation was 17.65 out of a maximum of 27 point (the scoring instrument used in these reviews excluded the power item and Cochrane-derived bias item). 21 Initial ratings for this review were conducted by the first four authors and two trained research assistants, using a Microsoft Access database designed for this symposium to calculate the DB score for each study. As a quality control measure, 20 % of studies were re-scored by the final author, and the inter-rater agreement for quality score using the modified DB tool was adequate (κ=0.67).…”
Section: Quality Assessmentmentioning
confidence: 99%